Reviving Phage Therapy for the Treatment of Cholera. (3rd November 2018) - Bhandare, Sudhakar; Colom, Joan; Baig, Abiyad; Ritchie, Jenny M; Bukhari, Habib; Shah, Muhammad A; Sarkar, Banwarilal L; Su, Jingliang; Wren, Brendan; Barrow, Paul; Atterbury, Robert J
Abstract: Cholera remains a major risk in developing countries, particularly after natural or man-made disasters. Vibrio cholerae El Tor is the most important cause of these outbreaks, and is becoming increasingly resistant to antibiotics, so alternative therapies are urgently needed. In this study, a single bacteriophage, Phi_1, was used to control cholera prophylactically and therapeutically in an infant rabbit model. In both cases, phage-treated animals showed no clinical signs of disease, compared with 69% of untreated control animals. Bacterial counts in the intestines of phage-treated animals were reduced by up to 4 log10 colony-forming units/g. There was evidence of phage multiplication only in animals that received a V. cholerae challenge. No phage-resistant bacterial mutants were isolated from the animals, despite extensive searching. This is the first evidence that a single phage could be effective in the treatment of cholera, without detectable levels of resistance. Clinical trials in human patients should be considered.